2023
DOI: 10.29333/ejosdr/13576
|View full text |Cite
|
Sign up to set email alerts
|

E-government development indices and the attainment of United Nations sustainable development goals in Africa: A cross-sectional data analysis

Samuel Olorunfemi Adams,
Chima Paul

Abstract: This paper explores the relationship between the United Nations (UN) e-government index (EGDI) and e-government development in Africa from 2010 to 2020 and forecasts the effect of e-government on the actualization of the sustainable development goals (SDGs) in Africa by 2030. To achieve the objectives, secondary data were collected on EDGI, online service delivery index (OSI), telecommunication infrastructure index (TII) and human capital index (HCI) from UN e-government survey spanning 2010-2020. The study ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
0
0
1
Order By: Relevance
“…The previous period derivation from long-run equilibrium is corrected in the current period in an adjusted speed of 4.8%; a percentage change in EXP is associated with a 29.13% increase in GDPG in an average ceteris paribus in the short-run; a percentage change in EXR is associated with a 19.66% increase in GDPG in an average ceteris paribus in the short-run; a percentage change in EXTR is associated with a 0.09% increase in GDPG in an average ceteris paribus in the short-run, a percentage change in IMP is associated with a 17.45% increase in GDPG in an average ceteris paribus in the short-run and a percentage change in M2 is associated with a 0.000292 increase in GDPG in an average ceteris paribus in the short-run. This findings corroborated with those from (Akaninyene, 2016;Akpan, 2009;Adams and Paul, 2023;Durdu, et al, 2007;Fapetu and Oloyede, 2014). Result from the short-run indicated that, a percentage increase in EXTR would bring about a 0.0009 percentage increase in GDPG; a percentage increase in EXR would bring about a 0.1966 percentage increase in GDPG; a percentage increase in EXP would bring about a 0.2913 percentage increase in GDPG; a percentage increase in M2 would bring about a 2.92E-06 percentage increase in GDPG; while a percent increase in IMP would bring about a 0.1745 percentage increase in GDPG.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…The previous period derivation from long-run equilibrium is corrected in the current period in an adjusted speed of 4.8%; a percentage change in EXP is associated with a 29.13% increase in GDPG in an average ceteris paribus in the short-run; a percentage change in EXR is associated with a 19.66% increase in GDPG in an average ceteris paribus in the short-run; a percentage change in EXTR is associated with a 0.09% increase in GDPG in an average ceteris paribus in the short-run, a percentage change in IMP is associated with a 17.45% increase in GDPG in an average ceteris paribus in the short-run and a percentage change in M2 is associated with a 0.000292 increase in GDPG in an average ceteris paribus in the short-run. This findings corroborated with those from (Akaninyene, 2016;Akpan, 2009;Adams and Paul, 2023;Durdu, et al, 2007;Fapetu and Oloyede, 2014). Result from the short-run indicated that, a percentage increase in EXTR would bring about a 0.0009 percentage increase in GDPG; a percentage increase in EXR would bring about a 0.1966 percentage increase in GDPG; a percentage increase in EXP would bring about a 0.2913 percentage increase in GDPG; a percentage increase in M2 would bring about a 2.92E-06 percentage increase in GDPG; while a percent increase in IMP would bring about a 0.1745 percentage increase in GDPG.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…b) Conectividad (Telecom Infrastructure Index [TII]): mide la infraestructura digital y el acceso a Internet de los ciudadanos. c) Capacidad humana (Human Capital Index[HCI]): mide las habilidades digitales de los ciudadanos y el personal del gobierno(Adams & Paul, 2023).Actas del II Congreso Internacional de Innovación, Ciencia y TecnologíaINUDI -…”
unclassified